Influence of blending proportions of Teak Sawdust and Cajuput leaves on characteristics of biomass pellets - Wassachol Wattana; Nattaya Montri; Manussavee Wongjanakul; Yingyot Naratta; Sansanee Duangjinda (My University, 2020)
Fuel pellets made from biomass is considered as a solid fuel that is also an alternative fuel which can substitute for the current fuels and can be considered as a fuel that has sustainable production. This research is the study of the production of fuel pellets from Teak sawdust blends with Cajuput leaves at five proportions by weight of Teak sawdust 100%, Cajuput leaves 100%, Teak sawdust 75% +Cajuput leaves 25%, Teak sawdust 50% +Cajuput leaves 50%, Teak sawdust 25% +Cajuput leaves 75% . The pellets were produced by a grinding and pelleting machine at three different speeds of 200, 250, and 300 rpm. After that, the quality of fuel pellets was evaluated by the physical properties as pellet dimensions, particles and bulk density, as well as moisture content and durability. The results show that blending proportion of Teak sawdust 75% and Cajuput leaves 25% provided the appropriate fuel pellet properties.
Keywords: Sawdust; Pellet; Pelletizing; Wood fuel; Solid fuel; null